An Economic Analysis of Sports Performance in an African and a South African Context - Fadal, Riyas (My University, 2011)
The South African Sports Confederation and Olympic Committee (SASCOC) have been criticised by the media for South Africa’s poor performance at the 2008 Beijing Olympics. Prior to the Olympic team’s departure SASCOC had anticipated that in all likelihood South Africa (SA) would be eligible for at least eight medals. The South African Olympic team returned from Beijing having won only a single silver medal. The failure of the Olympic team was described as a symptom of a lack of sufficient resources, a lack of prioritisation in resource allocation, and a lack of quality administration failing to identify talented individuals. The purpose of this study is to develop further insight into the socio-economic and organisational determinants that have impacted on South African sports performance. May (1997) propounds that a country’s success in sports is directly related to the economic resources that are available for those sports. However factors that are used to determine the levels of success for developed countries are not necessarily the same, or bear the same weight, as for developing countries. The premise of this study is to identify specific factors that increase success in sports in developing countries, or to at least identify factors which hinder sports performance in developing countries. In this exploratory research, the methodology includes a sequential two-phased mixed-method approach. The first phase of the research includes the development of an econometric model utilising variables identified in the literature review. The data collected and interpreted together with the literature review forms the basis of the semi-structured interview, i.e. phase two. This study finds evidence that suggests that South Africa’s performance in sports is dependent on socio-economic and organisational determinants. However the results of the study suggest that South Africa has sufficient resources to compete internationally if appropriately mobilised. The failure of the South African Olympic team is attributed to the inherent weakness of the institutions within South Africa. This study uniquely shows that sports performance is resource dependent; and is especially dependent on the appropriate investment in education and health. Furthermore, South Africa is inefficient in its utilisation of resources when compared to other African countries as relatively resource deficient African countries often perform better in sports than South Africa
MBA - WBS
Keywords: Sports performance; SASCOC